Разложите многочлен на множители пожалуйста!!!
Ответы
Объяснение:
1)ах+ау+bx+by=a(x+y)+b(x+y)=а+b
2)ах-ау+bx-by=a(x-y)+b(x-y)=a+b
3)a^2+ab+ac+bc=a(a+b+c)+bc
4)ax+ay+6x+6y=a(x+y)+6(x+y)a+6
5) 1-bx-x+b=1-x(b+1)+b
6)ab+2b-2a-4=b(a+2)-2(a-2)
7)x^2+xy+ax+ay=x(x+y+a)+ay
8)am-an+m-n=a(m-n)+m-n
9)3x-3y+ax-ay=3(x-y)+a(x-y)=3+a
10)ab-a^2+2a-2b=a(b-a)+2(a-b)
1,2,4,9 сокращаешь то, что в скобках
Ответ:
В решении.
Объяснение:
2.107
1) ax+ay+bx+by=
=(ax+ay)+(bx+by)=
=a(x+y)+b(x+y)=
=(x+y)(a+b);
2) ax-ay+bx-by=
=(ax-ay)+(bx-by)=
=a(x-y)+b(x-y)=
=(x-y)(a+b);
3) a²+ab+ac+bc=
=(a²+ab)+(ac+bc)=
=a(a+b)+c(a+b)=
=(a+b)(a+c);
4) ax+ay+6x+6y=
=(ax+ay)+(6x+6y)=
=a(x+y)+6(x+y)=
=(x+y)(a+6);
5) 1-bx-x+b=
=(1+b)-(x+bx)=
=(1+b)-x(1+b)=
=(1+b)(1-x);
6) ab+2b-2a-4=
=(ab+2b)-(2a+4)=
=b(a+2)-2(a+2)=
=(a+2)(b-2);
7) x²+xy+ax+ay=
=(x²+xy)+(ax+ay)=
=x(x+y)+a(x+y)=
=(x+y)(x+a);
8) am-an+m-n=
=(am-an)+(m-n)=
=a(m-n)+(m-n)=
=(m-n)(a+1);
9) 3x-3y+ax-ay=
=(3x-3y)+(ax-ay)=
=3(x-y)+a(x-y)=
=(x-y)(3+a);
10) ab-a²+2a-2b=
=(ab-a²)-(2b-2a)=
=a(b-a)-2(b-a)=
=(b-a)(a-2).